Examining cognitive absorption process on mobile information visualization: a conceptual framework/ Nora'ayu Ahmad Uzir ... [et al.] - Ahmad Uzir, Nora'ayu; Khairuddin, lrni Eliana; Ahmad, Norzuraiza Rina; Pati Khan, Mazlina; Abdullah, Siti Nurul Maryam (Faculty of Information Management, Universiti Teknologi MARA, 2014)
As the use of visualization becomes more wide-spread, a study in mobile information visualization in assisting cognitive absorption for knowledge exploratory and certain mobile information visualization model concerning to the subject area must be developed. Information Visualization (InfoVis) is an important asset in this set of tools. The effective delivery of abstract information is an important but challenging task in the design of effective mobile learning environments. Hence, the purpose of this study is to examine the effectiveness of mobile information visualization in expediting cognitive absorption in knowledge exploratory. This study uses experimental design to examine the effects of cognitive absorption in mobile information visualization towards learning outcome and to examine the efficiency of mobile information visualization in optimizing learning outcome. Finally, it uses the experimental result and literature review to develop a theoretical framework of mobile information visualization that support cognitive absorption in optimizing learning outcome. Results of this study would include new knowledge on mobile information visualization. These results are expected to leads towards the development of theoretical model for mobile information visualization that support cognitive absorption in optimizing learning outcome. After the introduction of background problem, this proposal will present the literature on mobile information visualization, cognitive absorption and e-learning outcome and describe the research methodology before presenting the expected results. This study contributes in mobile information visualization modelling. It will accelerate the cognitive absorption in knowledge exploration in optimizing learning outcome through mobile information visualization.